Relationship between Central Sensitization and Clinical Features of Migraine - Sambini, Felipe Daniel; Tolentino, Gabriella de Almeida; Norato, Adrila de Cassia Cabral; Juliana Pradela; Fabiola Dach; Grossi, Debora Bevilaqua (Headache Medicine, 2023)
Full abstract in PDF.